Estudo observacional de parâmetros meteo-oceanográficos na costa paraense: subsídio ao estudo de blooms de Sargassum sp. No litoral Amazônico - AMORIM, João Pedro Mancio de (2019)
The region of Salinópolis, one of the main tourist centers in the state of Pará, located on northeast, presented, during May 2014 and April 2015, episodes of macroalgae blooms of the genus Sargassum sp. In the present work, the objective was to evaluate the role of wind and regional ocean surface currents in the occurrence of macroalgal blooms on the Amazon coast, in order to identify patterns favorable to the transport of these organisms. Data provided by a conventional meteorological station, located in the municipality of Tracuateua-PA, in the period 1993-2015 were used, as well as monthly reanalysis data for the following variables: sea surface temperature-SST (OISST V2), wind circulation at 10 meters (MERRA) - both between 1983-2015 - and superficial ocean currents (GLORYS2V4) between 1993 and 2015, to the portion of the equatorial Atlantic delimited between 60 ° W, 5 ° S, 15 ° E and 15 ° N. The physical conditions from 2014 to 2015, especially the months of the events, were analyzed considering, as reference, the average state obtained through the historical series. The precipitation in the region presented extreme values during the first semester of both years, with blooms months being classified as extremely rainy (+82,91 mm in May 2014 and +211,62 mm in April). The results obtained for the SST anomalies were not related to blooms events, bult also, there were similarities between the field of surface wind anomalies and the field of ocean currents anomalies. In both cases, the direction of mass propagation was directed towards to Pará’s coast, representing a liquid transport in the North-South direction. In addition, a strong influence of the Intertropical Convergence Zone on the coast during the months of occurrence indicates that convective precipitation may also be associated with blooms events. The results obtained also suggest that the algae stranded in Salinópolis came, possibly, from a Sargassum sp. spot located north of the Amazon River mouth, on Atlantic ocean. Thus, these events, which occurred during the rainy season of the region, are possibly associated with combined effects of mass propagation transport in the north-south direction and convective precipitation, being these factors such good indicators of the occurrence of the phenomena.